Determination the Heating Rate and the Characteristic Age for Pulsars Stars - A.Abdulla Albakri, Sundus; H. Al-dahlaki, Hasanain; Abd-Almalik, Talib (Iraqi Journal of Science, 2023)
Pulsar stars are rotating Neutron stars can be divided into two types Millisecond and Normal Pulsars. In this work the magnetic field are concentrated depends on the period (P), and Period derivative (P) for a sample Normal, Millisecond and Radio stars which adopted. In addition, the values of spin down luminosity and Heating rate are determined by depending on (Ostriker and Gunn) model. The results showed that older Millisecond define as having greater ages specified how long pulsars lives at that ages very long period pulsars to be observable have particularly large surface magnetic field. The results indicate that spin down of luminosity for Millisecond and Normal star must due to the main energy loss rotation axis to align with magnetic axis as pulsar age. In addition, the Heating rate decreases with the star’s age, beside Characteristic age calculated.